Bean recipes: best food choice for the adventurous cook - Natabirwa, HN; National Agricultural Research Laboratories; Katende, D; National Agricultural Research Organization, Uganda; Lung'aho, Mercy G.; National Crop Resources Research Institute, Uganda; Pan-Africa Bean Research Alliance (2014)
A growing trend of malnutrition is currently a major public health concern in both lower and higher socio-economic levels. While malnutrition is popularly understood as undernutrition, it is also manifested as overnutrition. Malnutrition has shown to be an important concern in women, children, and the elderly in Uganda. Nutrition-specific interventions have been proven to effectively manage malnutrition among the populations. Appropriate measures include providing balanced nutrients through standard recipes among others. Improving the awareness of nutritious meal preparations and establishing long-term habits of balancing recipes could have a positive effect on malnutrition, potentially increasing a consumer's potential to meet nutritional requirements. Many parts of Uganda, and among age categories, have access to a surplus of nutritious beans. Beans are rich sources of vital nutrients which include high protein (18– 30%) and soluble fibre important for improving bowel movement of food and control of diabetes. Besides, they provide iron, zinc, folic acid, magnesium, manganese and B-vitamins. So often however, beans are consumed in a single form by almost every individual, especially at household level. When this consumption habit is combined with limited forms of preparation, quantities consumed seldom meet nutritional requirements. This bean recipe book is a collective research effort to add value to beans through simple preparation methods. It is a collection of recipes prepared in forms of sauces, snacks, bakery products, salads and soups. The recipes herein can be prepared basically by anyone, and are suitable for all individuals who utilize beans especially to derive nutritional benefits from them.